2000
DOI: 10.1083/jcb.149.7.1443
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Unique Roles of Cap23 and Gap43 in Actin Regulation, Neurite Outgrowth, and Anatomical Plasticity

Abstract: CAP23 is a major cortical cytoskeleton–associated and calmodulin binding protein that is widely and abundantly expressed during development, maintained in selected brain structures in the adult, and reinduced during nerve regeneration. Overexpression of CAP23 in adult neurons of transgenic mice promotes nerve sprouting, but the role of this protein in process outgrowth was not clear. Here, we show that CAP23 is functionally related to GAP43, and plays a critical role to regulate nerve sprouting and the actin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
210
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 33 publications
5
210
0
2
Order By: Relevance
“…Both proteins play a critical role in regulating neuritic outgrowth as well as the actin cytoskeleton and BASP1 can functionally substitute for GAP-43 in vivo. 64 Our results for BASP1 expression complement recent findings by Prabakaran et al 16 who also demonstrated a > 2-fold increase in BASP1 expression in the white matter of schizophrenic brains. Interestingly, reductions in GAP-43 gene and protein expression have been reported in the SCZ and BPD brain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both proteins play a critical role in regulating neuritic outgrowth as well as the actin cytoskeleton and BASP1 can functionally substitute for GAP-43 in vivo. 64 Our results for BASP1 expression complement recent findings by Prabakaran et al 16 who also demonstrated a > 2-fold increase in BASP1 expression in the white matter of schizophrenic brains. Interestingly, reductions in GAP-43 gene and protein expression have been reported in the SCZ and BPD brain.…”
Section: Discussionsupporting
confidence: 90%
“…63 It is a cytoskeleton-associated, calmodulin-binding protein that is widely and abundantly expressed during brain development, maintained in selected brain structures in the adult and reinduced during nerve regeneration. 64 BASP1 is functionally related to GAP-43. Both proteins play a critical role in regulating neuritic outgrowth as well as the actin cytoskeleton and BASP1 can functionally substitute for GAP-43 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, strong ANX2 immunoreactivity was found in the growth cones, as identified by its morphology and GAP43 staining (Fig. 5a), a growth cone enriched protein (Skene 1989;Frey et al 2000). ANX2 also co-localized with TUC-4 (Fig.…”
Section: Anx2 Is Concentrated In Growth Cones and Cultured Neuronal Tmentioning
confidence: 89%
“…20 GAP-43 also plays a role in sprouting responses associated with adult plasticity. 21 GAP-43 is expressed along with BDNF in response to neuronal injuries and is upregulated in granule cells following BDNF treatment. 22,23 In the present study, we test whether GAP-43 is an essential downstream effector of positive AMPA receptor modulators and subsequent BDNF-induced responses.…”
mentioning
confidence: 99%